Transformasi Perilaku Konsumen Parfum Lokal: Peran Live Streaming dan e-WOM dalam Mendorong Keputusan Pembelian Mykonos - Lingga Adi Setyawan; Lingga Yuliana (Jurnal Ilmiah Global Education, 2026)
This study aims to examine the influence of live streaming and electronic word of mouth on purchase decisions using a case study of Mykonos. Understanding the effectiveness of digital communication strategies for local brands is crucial in this study. The research method is quantitative. The sampling technique used is purposive sampling. A total of 104 respondents domiciled in Greater Jakarta (Jabodetabek) aged 17-50 years were involved in this study. The study was conducted in November 2025. Respondents were male and female social media users who had previously purchased Mykonos products online. The data source used primary data by distributing questionnaires through Google Forms. The data analysis technique used Partial Least Squares with the data processing tool SmartPLS version 4.1.0.0. The results showed that live streaming had a positive and significant effect on purchase decisions as the first hypothesis. Meanwhile, the second hypothesis indicated that electronic word of mouth had a positive and significant effect on purchase decisions. Mykonos needs to optimize its live streaming experience by featuring credible hosts, interactive content, and sensory storytelling to offset the limitations of the scent experience. Furthermore, the company needs to proactively manage eWOM by encouraging authentic reviews, monitoring digital conversations, and strengthening its user community to build reputation and enhance brand trust.